Peran Ekonomi Keluarga Dalam Membentuk Pendidikan Anak - Nurul Afifah Ainun; Ari Rahayu; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Education is important in human life. It lasts throughout a person's life and takes three forms: formal education, non-formal education and informal education. Therefore, the researcher would like to examine the role of family economics in shaping children's education, the impact of children's learning motivation in relation to family economic stability, and the relationship between the role of family economics and parental education in shaping children's education. The purpose of this research is to find out the role of the family economy on children's education. The methodology used is descriptive, which is qualitative research involving observation, interviewing, documenting and drawing conclusions. Based on the findings of this study, in Teluk Pandan Village, the economic role of each family or parent is very influential on the formation of their children's education. So that quite a lot of some families work hard for the education of their children.